Photoelectrocatalysis Activity TiO2/Ti electrode doped with N and Ni deposition for Congo Red Degradation - Edihar, Muh; Irwan, Irwan; Lidong, Andini (Asian Journal of Environmental Research, 2024)
The TiO2/Ti electrode was successfully synthesized by combining element N and metal Ni on the TiO2 matrix to degrade the organic compound Congo Red under UV-visible radiation. The aim of this study is to obtain Ni@N-TiO2/Ti electrodes and test their performance in degrading Congo Red dye under UV-visible light radiation. The Ni@N-TiO2/Ti electrode was prepared using the Sol-Gel and electrodeposition methods. The presence of nitrogen in N-TiO2 is determined by FTIR and detected at a wavelength of 1.064 cm1. The analysis of UV-Vis DRS indicates an energy gap of 3.06 eV for N-TiO. XRD analysis revealed anatase crystal structure formation and nickel's presence in the Ni@N-TiO2/Ti electrode detected at 2θ 52.8°. The usage characteristics of linear sweep voltammetry indicate that the TiO2/Ti electrode is active under UV light, while the Ni@N-TiO2/Ti electrode is active under visible light. An electrode activity test using the multi-pulse amperometry method showed that the photoelectrocatalysis performance of Ni@N-TiO2/Ti under visible light radiation reached an ideal degradation rate of 36%.